OPTIMALISASI PELAKSANAAN PROYEK PEMBANGUNAN JALAN TOL MENGGUNAKAN METODE CRITICAL PATH METHOD (CPM) PT. HUTAMA KARYA (Studi Kasus Jalan Tol Pekanbaru-Padang Seksi 2 STA 55+225 s.d 59+250) - Sihombing Hotmario Asi; Samsir Samsir; Marpaung Jonnes M Rio (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Project development planning certainly requires proper analysis and inaccordance with the desired needs. This activity is very necessary because itmeasures how much it will cost and how much it costs to build the project. Roadconstruction in Indonesia is currently growing rapidly, especially in the currentera. The success or failure of the implementation of road construction projects isoften due to the lack of planned project activities and ineffective control so thatproject activities are not efficient. Optimization of development time aims toprevent project delays and minimize costs and accelerate development projectactivities. In the toll road construction project the Pekanbaru Padang Toll roadconstruction work in section 2 STA 55+225 to 59+250 using the CPM methodthere is a critical path where the work activities are land acquisition work,construction work for kit and warehouse directors, foundation work, column work, Stressing girder work, slab work, asphalt coating work, other work and finishingwork. The scheduled duration of the project is 385 days, but after being evaluatedand analyzed by the CPM method, the project can be completed within 374 days.This means that the project can be done 11 days earlier than the specifiedschedule. Keywords: Project Management, Scheduling Optimization, CPM